EXTH-53. IL-12 ARMORED CAR T CELL THERAPY FOR HETEROGENEOUS GLIOBLASTOMA. (14th November 2022) - Shen, Steven; Cook, Sarah; Suryadevara, Carter; Hotchkiss, Kelly; Snyder, David; Sanchez-Perez, Luis; Sampson, John
Abstract: INTRODUCTION: Chimeric antigen receptor (CAR) T cells specific for the glioblastoma (GBM)-specific epidermal growth factor receptor variant III (EGFRvIII; CARvIII) have successfully treated tumors homogeneously expressing EGFRvIII when combined with lymphodepletion, however this is not recapitulated clinically. We generated an "armored" CARvIII which constitutively secretes IL-12, a stimulatory cytokine that enhances T cell persistence and function, that is capable of treating orthotopic heterogeneous GBM in immune competent mice. METHODS: C57Bl/6 mice were intracranially (IC) implanted with 5 x 10 5 of either homogenous (CT2AvIII) or heterogeneous (1:1 CT2AvIII and CT2A parental) tumor cells. Mice were treated with 2 x 10 6 CARvIII or IL-12 CARvIII seven days post tumor implant and monitored for survival. TCRα  -/-, CD8 -/- and C57Bl/6 mice were IC implanted with homogeneous or heterogeneous tumors and treated 7 days post implant with intracranial IL-12 CARvIII therapy to assess the role of endogenous T cells. T cells within the tumor microenvironment were characterized by flow cytometry days 8, 14, and 17 post tumor implantation. RESULTS: IL-12 CARvIII cells were successfully generated, secreted IL-12, and were cytotoxic against EGFRvIII-expressing tumor cells in vitro . IL-12 CARvIII therapy was curative in homogenous CT2AvIII tumors (p< 0.0001) and conferred a long-term survival in 50% of mice with heterogeneous CT2AvIII:CT2A parental tumors in vivo (p< 0.0001). Furthermore, IL-12 CARvIII therapy successfully eradicated the homogeneous CT2AvIII tumors in TCRα  -/- and CD8 -/- mice but failed to produce any efficacy against the heterogeneous CT2AvIII:CT2A parental tumors (p=0.0002). Endogenous T cells in IL-12 CARvIII treated mice were found to be more migratory, and interestingly more exhausted than in CARvIII treated mice. CONCLUSIONS: Our findings show that IL-12 CARvIII can effectively eradicate IC homogenous tumors without lymphodepletion. Surprisingly, IL12 CARvIII therapy also treated IC heterogeneous glioma. Heterogeneous tumor clearance required an endogenous CD8 T cell response.